Unlocking New Horizons: Teacher Mobility and Competence Growth via Erasmus Exchange Programs - Ioana-Simona Ivasciuc; Nicolae Marinescu; Ana Ispas (Education Sciences, 2025)
This qualitative study investigates how short-term international mobility—specifically Erasmus staff exchange—nurtures educational leadership in an increasingly globalized landscape. Drawing on in-depth interviews with 55 educators from European and non-European countries, the research traces the ways mobility experiences reshape professional practice, career trajectories and institutional engagement. Findings show that time abroad enhances intercultural competence, global awareness, and pedagogical innovation—capabilities central to educators who must lead learning in diverse, rapidly evolving contexts. Participants described a renewed sense of purpose and an expanded leadership identity on reentry, positioning mobility as both a personal and systemic catalyst. Nonetheless, persistent barriers—including financial constraints, language proficiency gaps, and uneven institutional support—continue to restrict mobility access. Addressing these inequities is imperative if Erasmus and similar programs are to serve as genuine engines of educational transformation rather than isolated opportunities for the already advantaged. By mapping the link between mobility, leadership growth, and institutional change, this article offers actionable insights for policy-makers and university leaders seeking to embed inclusive, innovation-oriented practices across local and international education systems.